Hybrid Circuit for Stimulated Bone Regrowth. (1983) - Govaerts, R.; Sansen, W.; de Dijcker, F.
Abstract : A hybrid circuit using a custom-designed I 2 L IC for a four-channel implantable biotelemetry system together with a HF transmitter has been designed. It realises a high-performance and economical device.